1989
DOI: 10.1111/j.1365-2621.1989.tb05949.x
|View full text |Cite
|
Sign up to set email alerts
|

Organic Acids as Tenderizers of Collagen in Restructured Beef

Abstract: Acetic, citric and lactic acid were incorporated into restructured beef steaks to determine their effect on collagen. These steaks were analyzed for collagen solubility, total collagen content, shear force behavior, sarcoplasmic and myofibrillar protein extractability, thermal stability and color. These results were compared to those obtained from control samples containing high collagen and low collagen. Results indicate that these acids increased collagen solubility, total collagen content and shear force va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
2
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 29 publications
3
28
2
4
Order By: Relevance
“…Regarding the instrumental color parameter Ôa* valueÕ, our result seemed supported with the statement of Arganosa and Marriott (1989) in which a* values were observed to be lower for lower pH meat, treated with lactic acid. Redness of the meat is represented by a* values (Van Laack, Berry, & Solomon, 1996), and hence the loss of redness shows decrease in a* values (Young & West, 2001) and vice-versa.…”
Section: Effect Of Lactic Acid Concentration On A* Values Of the Fressupporting
confidence: 92%
“…Regarding the instrumental color parameter Ôa* valueÕ, our result seemed supported with the statement of Arganosa and Marriott (1989) in which a* values were observed to be lower for lower pH meat, treated with lactic acid. Redness of the meat is represented by a* values (Van Laack, Berry, & Solomon, 1996), and hence the loss of redness shows decrease in a* values (Young & West, 2001) and vice-versa.…”
Section: Effect Of Lactic Acid Concentration On A* Values Of the Fressupporting
confidence: 92%
“…Protein denaturation in the presence of acid would decrease protein solubility and the protein in acid-treated samples would be less likely to be washed away during vacuum-tumbling. Similar effects were reported for restructured beef (Arganosa and Marriott 1989).…”
Section: Moisture Fat and Proteinsupporting
confidence: 88%
“…Acids also affect physical properties such as shear force, water holding capacity, drip loss, cook loss, juiciness, pH, as well as microbial stability or shelflife (Arganosa and Marriott 1989;Fletcher 1999).…”
Section: Atfish Farmers Frequently Encounter a Flavor Problem Withmentioning
confidence: 99%
“…)80 1981) to 6.3 (Yu and Lee, 1986). Furthermore, several studies have shown that enhancement with organic acids reduces shear force values and improves sensory panel tenderness ratings of cooked beef (Arganosa and Marriott, 1989;Eilers et al, 1994;Aktaç ft al., 2003). In particular.…”
Section: Cooking Characteristics and Sensory Attributesmentioning
confidence: 96%